HISTOGRAM E QUALIZATION SMOOTHING FOR DETERMINING THRESHOLD ACCURACY ON ANCIENT DOCUMENT IMAGE BINARIZATION - Mahendar Dwipayana; Fitri Arnia; Zuhar Musliyana (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
Ancient documents are inheritance that must be preserved. Thedocuments contain historical, scientific, social, religious information, etc.Converting ancient documents into digital image formats is one of ways topreserve the inheritance and can be stored into a computer. However,images of ancientdocuments have many blemishes caused by age,moisture, flood, etc. Therefore, special techniques are needed for thoseimages to be restored and can improve the legibility of the ancientdocuments’ images. In this study, the image restoration process usesseparation of background and foreground/text on histogram equalizationsuch as research conducted by Fitri Arnia in 2008. Through histogramequalizationimages can be seen the distribution of pixels from the intensityof black color "0" to white "1". The distribution of pixels on histogramequalization describes the curves of foreground/text and curves ofbackground. Among the histogram curves, the determination ofthresholdvalues can be done so as to clarify the foreground/text andbackground areas on images of ancient documents. The lowest pointbetween the two curves is the lowest pixel (local minima) which is used asthe threshold value. However, the selection of such threshold values insome cases is very difficult to determine because there are still manyfluctuations in the curve at the lowest curve. Therefore, this studyproposesa histogram smoothing method in the ancient documents’ imagesto minimize curvature fluctuations and to determine more accuratethreshold values. In this research, average filtering method is used forsmoothing the histogram image. This filter successfully refines thehistogram and makes the image of the restoration or binary image displaythe value of the ancient document image readability increases.Keywords: HistogramEqualization, Smoothing Histogram, AverageFiltering, Thresholding